Evaluasi Penerimaan Orang Tua Sistem PPDB Online Menggunakan Pendekatan Teori Technology Acceptance Model (TAM) Di Kabupaten Bantul - Sri Mulyatun; Sri Ngudi wahyuni (Jurnal Dinamika Informatika, 2019)
This study measures the perceptions of perception and benefits of PPBD online Systems base on zonation for parents of prospective students in ease of use in Piyungan High School and Pathuk Gunungkidul High School. Samples were taken at two schools which were divided into one rayon. the audiences of this research are the parents of prospective students who use the zoning-based PPDB online system. This research aim is to measure the ease and benefits of the online PPDB system in the area so that it can be used as a decision-making material in the future. The Data Analysis uses a quantitative study of multiple regression methods by testing the value of f as for the variables to be evaluated are the Perceived Usefulness variable and the Perceived Ease of use variable.